1984
DOI: 10.1159/000249664
|View full text |Cite
|
Sign up to set email alerts
|

Etretinate (Tigason) Hepatitis in 2 Patients

Abstract: A histologically confirmed, clinically inapparent and reversible hepatitis occurred in 2 patients (1 psoriasis, 1 basal cell nevus syndrome) within the first months after introduction of etretinate therapy. Causes of hepatitis other than etretinate were not found. Reintroduction of etretinate resulted in reactivation and/or persistance of the hepatitis in both patients. These data strongly suggest that the hepatitis in both patients was caused by etretinate. Later the basal cell nevus syndrome patient was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…With the exception of 2 cases [6. 13], patients reported with etretinate-associated hepatitis have been middle-aged or elderly females [4,5,7,9,14,15], That case, a 39-year-old male who had previously received methotrexate, was HLA-A1, as was our patient.…”
Section: Discussionmentioning
confidence: 53%
“…With the exception of 2 cases [6. 13], patients reported with etretinate-associated hepatitis have been middle-aged or elderly females [4,5,7,9,14,15], That case, a 39-year-old male who had previously received methotrexate, was HLA-A1, as was our patient.…”
Section: Discussionmentioning
confidence: 53%
“…Thirdly. the fact that the run�lionally c1ose1y retated compounct isotretinoin produced no apparent hepatic reaction (although other side-effects were noted) indicates that the etretinate-associated hepatitis was due to a drug specific, idiosyncratic reaction which has also been noted by van Voorst-Vader et al (5). Fourthly, slight to moderate structural and functional abnormali ties of the !iver may persist after etretinate-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 60%
“…Literature regarding hepatotoxicity of etretinate is con flicting. Recently, Van Voorst Vader et al [15] reported hepatitis in 2 patients within the first months after introduction of etreti nate therapy. Etretinate has been shown to induce occasionally transient increases in transaminases (for example Mahrle et al [7]).…”
Section: Discussionmentioning
confidence: 99%